Polyethersulfone (PES)/cellulose acetate butyrate (CAB) composite hollow fiber membranes for BTEX separation from produced water. Issue 128 (14th December 2015) - Zha, Shangwen; Yu, Jianjia; Zhang, Guoyin; Liu, Ning; Lee, Robert
Abstract : Polyethersulfone (PES)/cellulose acetate butyrate (CAB) composite hollow fiber membranes were prepared by dry-jet wet-spinning for BTEX (benzene, toluene, ethylbenzene and xylene) separation from oilfield produced water. Abstract : Polyethersulfone (PES)/cellulose acetate butyrate (CAB) composite hollow fiber membranes were prepared by dry-jet wet-spinning for BTEX (benzene, toluene, ethylbenzene and xylene) separation from oilfield produced water. The effects of pore agent contents and air gaps on hollow fiber membrane morphology, permeate water flux, BTEX rejection efficiency and especially, membrane antifouling ability were investigated. It was found that the inner layer surface of the PES/CAB hollow fiber membrane became thicker and more porous with the increase of air gap size. When the air gap reached 4 cm, a very dense skin layer formed at the outer surface of the membrane. As the pore formation agent content increased from 1% to 5%, the specific surface area, pore size and permeate water flux of the membrane all increased, although rejection efficiency was slightly sacrificed. Our results also revealed that membranes prepared with larger air gaps showed a higher fouling tendency, and those with lesser air gaps exhibited better antifouling ability. The PES/CAB hollow fiber membrane prepared with 5% pore formation agent and a 4 cm air gap showed 82.1–84.6% rejection of BETX accompanied by favourable permeate water flux, which is promising for the potential application in BTEX removal from produced water.